Vitamin K1 attenuates bile duct ligation-induced liver fibrosis in rats. (June 2014) - Jiao, Kun; Sun, Quan; Chen, Baian; Li, Shengli; Lu, Jing
Abstract Vitamin K1 is used as a liver protection drug for cholestasis-induced liver fibrosis in China, but the mechanism of vitamin K1's action in liver fibrosis is unclear. In this study, a model of liver fibrosis was achieved via bile duct ligation in rats. The rats were then injected with vitamin K1, and the levels of serum aspartate aminotransferase, alanine transaminase, total bilirubin and the fibrotic grade score, collagen content, the expressions of α-smooth muscle actin (SMA) and cytokeratin 19 (CK19) were measured on day 28 after ligation. The levels of the biochemical parameters, fibrotic score and collagen content were significantly reduced by treatment with vitamin K1 in bile duct-ligated rats. In addition, α-SMA and CK19 expression was significantly reduced by vitamin K1 treatment in bile duct-ligated rats. These results suggested that vitamin K1 may attenuate liver fibrosis by inhibiting hepatic stellate cell activation in bile duct-ligated rats.